Diaphragm and preparation method thereof, secondary battery and electric device
By using a combination of carboxy modified diamond, aluminate coupling agent, carboxylate compound and binder of a specific mass ratio, the problems of poor wettability and low interface performance of the polyolefin separator are solved, and the secondary battery is improved Cycling performance and stability.
Patent Information
- Application Number
- CN202411677334.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing polyolefin separators have problems such as poor wetting and low interface performance in secondary batteries, resulting in a degradation of the cycling performance of the battery.
Using a combination of carboxy modified diamond, aluminate coupling agent, carboxylate compounds and binders of specific mass ratios, the binding force and wetting properties of the membrane are enhanced through chemical bonding and synergistic effects, and the mechanical properties are improved. Electrolyte affinity.
It improves the wettability and interface performance of the diaphragm, enhances the capacity, Coulomb efficiency and cycle stability of the secondary battery, and prevents the diaphragm from breaking and damage during charging and discharging.
Smart Images

Figure CN119208917A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a diaphragm and a preparation method thereof, a secondary battery, and an electrical device. Background Art
[0002] With the rapid development of new energy vehicles, portable electronic devices and other electrical devices, secondary batteries, as key energy storage devices, have become the focus of scientific research and industry in terms of energy density, cycle performance and safety performance. The diaphragm is one of the important components of secondary batteries. The diaphragm is a thin film that separates the positive and negative electrodes during the electrolytic reaction and prevents the loss of energy in the direct reaction. The performance of the diaphragm determines the interface structure and internal resistance of the battery, which directly affects the battery's capacity, cycle and safety performance.
[0003] At present, the most widely used separator is polyolefin separator, which is widely used due to its advantages of light weight, flexibility and easy processing. However, due to its inherent structural characteristics, surface hydrophobicity and low softening temperature, polyolefin separator has the disadvantages of poor wettability and low interface performance, which leads to the decline of battery cycle performance. Summary of the invention
[0004] Based on this, the present application provides a diaphragm and a preparation method thereof, a secondary battery, and an electrical device. The diaphragm provided in the present application has good wettability and interface performance, thereby being able to effectively improve the cycle performance of the secondary battery.
[0005] In a first aspect of the present application, a diaphragm is provided, comprising carboxyl-modified diamond, an aluminate coupling agent, a carboxylate compound, and a binder in a mass ratio of (0.04-0.06):(0.8-1.2):(0.2-0.3):(0.4-0.6);
[0006] Wherein, the carboxylic acid ester compound includes one or more compounds having the structure shown in formula (I):
[0007] ; R 11 and R 12 Each independently selected from C3~C 10 Alkyl or C3~C 10 Ar is selected from S1 substituted or unsubstituted C6~C 20 Aromatic group; S1 is selected from C1~C 10 Alkyl, C1~C 10 Haloalkyl or ; R 13 Selected from C3~C 10 Alkyl or C3~C 10 Halogenated alkyl.
[0008] In one embodiment, R 11 and R 12 Each is independently selected from C3~C8 alkyl; Ar is selected from C6~C 10 Aromatic group.
[0009] In one embodiment, the carboxylic acid ester compound includes one or more compounds having the structure shown in formula (II): ; m1 and m2 are each independently 1, 2, 3, 4 or 5.
[0010] In one embodiment, the aluminate coupling agent includes one or more of aluminate coupling agent LS60, aluminate coupling agent LS62, aluminate coupling agent LS821 and aluminate coupling agent NXH-821.
[0011] In one embodiment, the binder includes one or more of polyvinylidene fluoride, styrene-butadiene rubber and carboxymethyl cellulose.
[0012] In one embodiment, the preparation steps of the carboxyl-modified diamond include:
[0013] Heat-treating the nanodiamond in air or oxygen environment to prepare the carboxyl-modified diamond;
[0014] The surface of the nano-diamond has one or more of hydroxyl, carbonyl and carboxyl functional groups; the process parameters of the heating treatment include: heating to 400°C~450°C at a heating rate of 3°C / min~5°C / min, and keeping the temperature for 4h~10h.
[0015] A second aspect of the present application provides a method for preparing the diaphragm according to any one of the embodiments of the first aspect of the present application, comprising the following steps:
[0016] Mixing the carboxyl-modified diamond, the aluminate coupling agent, the carboxylate compound and the binder in a solvent to prepare a mixed slurry;
[0017] The mixed slurry is formed into a film and dried to prepare the separator.
[0018] In one of the embodiments, in the mixed slurry, the mass volume ratio of the aluminate coupling agent to the solvent is (0.005~0.1) g:1 mL.
[0019] In a third aspect of the present application, a secondary battery is provided, comprising a positive electrode sheet, a negative electrode sheet, a separator separated between the positive electrode sheet and the negative electrode sheet, and an electrolyte; the separator is the separator described in any embodiment of the first aspect of the present application.
[0020] A fourth aspect of the present application provides an electrical device comprising the secondary battery described in the third aspect of the present application.
[0021] The diaphragm provided in the present application has at least the following beneficial effects:
[0022] The diaphragm provided in the present application includes carboxyl modified diamond, aluminate coupling agent, carboxylate compound and binder in a specific mass ratio. Among them, the aluminate coupling agent can form a chemical bond between the carboxyl modified diamond and the binder to enhance the binding force and bonding strength between the components. The carboxylate compound of a specific structure cooperates with the carboxyl modified diamond to adjust the mechanical properties of the diaphragm. Further assisted by a binder, the internal binding force of the diaphragm is increased and the diaphragm structure is more stable, which helps to prevent the diaphragm from rupture and damage during the charge and discharge process of the battery, thereby ensuring the stability of the battery. In addition, the polar groups of the carboxylate compound and the organic groups in the aluminate coupling agent can interact with the polar analysis in the electrolyte or the organic solvent in the electrolyte to enhance the affinity of the diaphragm to the electrolyte, thereby improving the wetting properties of the diaphragm.
[0023] In summary, the diaphragm provided in the present application can effectively improve the wettability and interface properties of the diaphragm by selecting a specific mass ratio of carboxyl-modified diamond, aluminate coupling agent, carboxylate compound and binder, so as to improve the electrochemical properties of the secondary battery such as capacity, coulombic efficiency and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the diaphragm prepared in Example 1 of the present application;
[0025] Figure 2 This is a real shot of the diaphragm prepared in Example 2 of the present application;
[0026] Figure 3 This is a performance diagram of the contact angle between the diaphragm prepared in Example 3 of the present application and the electrolyte;
[0027] Figure 4 The diaphragms prepared in Example 1 and Comparative Example 1 are assembled into silicon negative electrode half-cells, and the cycle performance diagram of the silicon negative electrode half-cell at a charge and discharge rate of 0.5C;
[0028] Figure 5 This is a real shot of the diaphragm prepared in Comparative Example 2 of the present application;
[0029] Figure 6 This is a real shot of the diaphragm prepared in comparative example 3 of the present application. DETAILED DESCRIPTION
[0030] The following is a further complete and clear description of the diaphragm and preparation method thereof, the secondary battery, and the electrical device of the present application in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0031] In the present application, the terms “further”, “furthermore”, “particularly”, etc. are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.
[0032] In this application, "optionally", "optional" and "optional" refer to optional, that is, to any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.
[0033] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1 to 10, indicating that t is any integer selected from the group of integers consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges included therein.
[0034] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0035] In this application, "alkyl" refers to a saturated hydrocarbon group containing primary (normal) carbon atoms, secondary carbon atoms, tertiary carbon atoms, quaternary carbon atoms, or a combination thereof. Phrases containing this term, such as "C3~C 10 "Alkyl" refers to an alkyl group containing 3 to 10 carbon atoms, and each occurrence can be independently C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl, C8 alkyl or C 10Alkyl. Suitable examples include, but are not limited to: 1-propyl (n-propyl, n-Pr, n-propyl, -CH2CH2CH3), 2-propyl (i-Pr, i-propyl, -CH(CH3)2), 1-butyl (n-butyl, n-Bu, n-butyl, -CH2CH2CH2CH3), 2-methyl-1-propyl (i-Bu, i-butyl, -CH2CH(CH3)2), 2-butyl (s-Bu, s-butyl, -CH(CH 3)CH2CH3), tert-butyl (1,1-dimethylethyl, 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH3)3), 1-pentyl (n-pentyl, n-pentyl, -CH2CH2CH2CH2CH3), 2-pentyl (-CH(CH3)CH2CH2CH3), 3-pentyl (-CH(CH2CH3)2), 2-methyl-2-butyl (-C(CH3)2CH2CH3), 3-methyl -2-butyl (-CH(CH3)CH(CH3)2), 3-methyl-1-butyl (-CH2CH2CH(CH3)2), 2-methyl-1-butyl (-CH2CH(CH3)CH2CH3), 1-hexyl (n-hexyl, -CH2CH2CH2CH2CH2CH3), 2-hexyl (-CH(CH3)CH2CH2CH2CH3), 3-hexyl (-CH(CH2CH3)(CH2CH2CH3)), 2-methyl-2-pentyl (-C(CH3)2CH2CH2CH3), 3-methyl-2-pentyl (-CH(CH3)CH(CH3)CH2CH3), 4-methyl-2-pentyl (-CH(CH3)CH2CH(CH3)2), 3-methyl-3-pentyl (-C(CH3)(CH2CH3)2) and 2-methyl-3-pentyl (-CH(CH2CH3)CH(CH3)2).
[0036] In the present application, "haloalkyl" means that on the basis of "alkyl", a halogen atom replaces the hydrogen atom in the alkyl group. It is understood that the number of halogen atoms substituted is ≤ the number of hydrogen atoms in the alkylene group. In the present application, "halogen atom" refers to F, Cl, Br or I.
[0037] In the present application, "aromatic group" refers to an aromatic hydrocarbon group derived from an aromatic ring compound by removing a hydrogen atom. It can be a monocyclic aromatic group, a condensed aromatic group, or a polycyclic aromatic group. For polycyclic rings, at least one is an aromatic ring system. Phrases containing this term, for example, "C6~C 20 "Aromatic group" refers to an aromatic group containing 6 to 20 atoms, each occurrence of which can be independently C6 aromatic group, C 10 Aryl. Suitable examples include, but are not limited to, benzene and naphthalene. "Arylene" refers to an aromatic hydrocarbon group derived from an aryl group by removing a hydrogen atom.
[0038] In the method of modifying polyolefin separators, some researchers have compounded inorganic materials with polyolefin separators to obtain separator materials. However, the chemical properties of inorganic materials and polyolefins are quite different, and the interfacial bonding force between the two is weak. This will cause the inorganic materials to easily fall off from the polyolefin separator during the use of the battery, affecting the stability and service life of the separator.
[0039] Based on this, the present application provides a diaphragm that does not contain polyolefin.
[0040] In a first aspect of the present application, a diaphragm is provided, comprising carboxyl-modified diamond, an aluminate coupling agent, a carboxylate compound and a binder in a mass ratio of (0.04-0.06):(0.8-1.2):(0.2-0.3):(0.4-0.6).
[0041] Wherein, the carboxylic acid ester compound includes one or more compounds having the structure shown in formula (I):
[0042] .
[0043] Compared with general inorganic oxide materials, diamond clusters have the advantages of large specific surface area, high porosity, good heat dissipation performance, and rich surface functional groups. The above advantages provide a broad space for its application in diaphragm materials. However, when nanodiamonds are directly applied to polymer-containing diaphragms, they still face many challenges, such as the uniformity of dispersion of nanodiamonds and polymers, the optimization of the structure and morphology of diaphragm materials, and the mechanism of improving electrochemical performance.
[0044] The present application uses carboxyl modified diamond, which has good compatibility with components such as aluminate coupling agent, carboxylate compound and binder, thereby overcoming the disadvantage of insufficient uniformity of inorganic material dispersion. In addition, the diaphragm provided by the present application includes carboxyl modified diamond, aluminate coupling agent, carboxylate compound and binder in a specific mass ratio. Among them, the aluminate coupling agent can form a chemical bond between the carboxyl modified diamond and the binder to enhance the binding force and bonding strength between the components. The carboxylate compound of a specific structure cooperates with the carboxyl modified diamond to adjust the mechanical properties of the diaphragm. Further assisted by a binder, the internal binding force of the diaphragm is increased and the diaphragm structure is more stable, which helps to prevent the diaphragm from breaking and damaging during the charge and discharge process of the battery, thereby ensuring the stability of the battery. Further, the polar groups of the carboxylate compound and the organic groups in the aluminate coupling agent can interact with the polar analysis in the electrolyte or the organic solvent in the electrolyte to enhance the affinity of the diaphragm to the electrolyte, thereby improving the wetting properties of the diaphragm.
[0045] In summary, the diaphragm provided in the present application can effectively improve the wettability and interface properties of the diaphragm and improve the electrochemical properties of the secondary battery, such as capacity, coulombic efficiency, and cycle stability, by selecting a specific mass ratio of carboxyl-modified diamond, aluminate coupling agent, carboxylate compound, and binder.
[0046] It can be understood that in the present application, the mass ratio of carboxyl-modified diamond, aluminate coupling agent, carboxylate compound and binder can be selected from any value between (0.04-0.06): (0.8-1.2): (0.2-0.3): (0.4-0.6). Specifically, the mass ratio of carboxyl-modified diamond, aluminate coupling agent, carboxylate compound and binder includes but is not limited to 0.04: 0.8: 0.25: 0.5, 0.045: 0.8: 0.25: 0.5, 0.05: 0.8: 0.25: 0.5, 0.053: 0.8: 0.25: 0.5, 0.054: 0.8: 0.25: 0.5, 0.060: 0.8: 0.25: 0.5, 0.061: 0.8: 0.25: 0.5, 0.062: 0.8: 0.25: 0.5, 0.063: 0.8: 0.25: 0.5, 0.064: 0.8: 0.25: 0.5, 0.065: 0.8: 0.25: 0.5 .055: 0.8: 0.25: 0.5, 0.058: 0.8: 0.25: 0.5, 0.06: 0.8: 0.25: 0.5, 0.04: 0.9: 0.25: 0.5, 0.045: 0.9: 0.25: 0.5, 0.05: 0.9: 0.25: 0.5, 0.053: 0.9: 0.25: 0.5, 0.054: 0.9: 0.25: 0.5, 0.055: 0.9: 0.25: 0.5, 0.058: 0.9: 0.25: 0.5, 0.06: 0.9: 0.25: 0.5, 0.04: 1: 0.25: 0.5, 0.045: 1: 0.25: 0.5, 0.05: 1: 0.25: 0.5, 0.053: 1: 0.25: 0.5 , 0.054:1:0.25:0.5, 0.055:1:0.25:0.5, 0.058:1:0.25:0.5, 0.06:1:0.25:0.5, 0.06:1:0.25:0.5, 0.06:1:0.25:0.55, 0.06:1:0.25:0.6 or 0.06:1.2:0.3:0.6, or the range consisting of the above two point values as end values.
[0047] In one example, R 11 and R 12 Each independently selected from C3~C 10 Alkyl or C3~C 10 Halogenated alkyl.
[0048] Furthermore, R 11 and R 12 Each independently selected from C3~C 10 Alkyl or C3~C 10 Halogenated alkyl.
[0049] Furthermore, R 11 and R 12 Each is independently selected from C3 to C8 alkyl. 11 and R 12 Each is independently selected from -CH2CH2CH2-, -CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2CH2CH2-, -CH2CH2CH2CH2CH2CH2CH2- or -CH2CH2CH2CH2CH2CH2CH2CH2CH2-.
[0050] In one example, Ar is selected from S1 substituted or unsubstituted C6~C 20 Aromatic group; S1 is selected from C1~C 10 Alkyl, C1~C 10 Haloalkyl or . R 13 Selected from C3~C 10 Alkyl or C3~C 10 Ar is selected from , , , , or .
[0051] Further, Ar is selected from C6~C 10 Aromatic group.
[0052] Furthermore, Ar is selected from .
[0053] In one example, the carboxylic acid ester compound includes one or more compounds having the structure shown in formula (II): ; m1 and m2 are each independently 1, 2, 3, 4 or 5.
[0054] Furthermore, the carboxylic acid ester compound includes , , , and One or more of .
[0055] For example, the carboxylic acid ester compound includes , , , , , , , and One or more of .
[0056] The above-mentioned carboxylic acid ester compounds are supplemented with carboxyl-modified diamond, which can improve the mechanical properties of the diaphragm and make the diaphragm easy to shape while maintaining a certain strength. Specifically, the π-π stacking of the aromatic groups in the structure can enhance the interaction between the internal components and structures of the diaphragm, thereby improving the mechanical strength of the diaphragm. And the ester groups contained therein can chemically cross-link with the functional groups on the surface of the carboxyl-modified diamond, or the ester groups contained therein can bind to the surface of the carboxyl-modified diamond through hydrogen bonding interactions, which not only enhances the cohesion of the diaphragm material, but also helps to construct a barrier that is conducive to the migration of lithium ions but blocks the direct passage of electrons, so as to enhance the overall stability of the diaphragm.
[0057] In addition, the ester group in the above-mentioned carboxylic acid ester compounds can give the diaphragm good thermal stability and low volatility. And the polar group ester group can interact with the polar molecules in the electrolyte to help form a stable SEI (solid electrolyte interface) layer, reduce side reactions, and thus improve the coulombic efficiency of the battery. Furthermore, the alkyl side chain increases the flexibility of the molecule and helps to regulate the wettability of the diaphragm material and the electrolyte to ensure proper ion conduction without causing liquid leakage.
[0058] In one example, the aluminate coupling agent includes one or more of aluminate coupling agent LS60, aluminate coupling agent LS62, aluminate coupling agent LS821 and aluminate coupling agent NXH-821.
[0059] The inventors of the present application have found, based on rich experience and a large number of experiments, that the type of coupling agent plays an important role in the compatibility of the components in the diaphragm. Other coupling agents such as aminosilane coupling agents have the disadvantage of insufficient diaphragm stability when combined with carboxyl-modified diamond. Aluminate coupling agents hydrolyze or contain functional groups that can hydrolyze to form Al-O bonds, which allows them to react with the carboxyl groups in carboxyl-modified diamond to adjust their compatibility with carboxyl-modified diamond. In addition, aluminate coupling agents also contain long-chain alkyl groups or other organic end groups, which can also enhance their compatibility with organic binders.
[0060] In one example, the binder includes one or more of polyvinylidene fluoride, styrene butadiene rubber and carboxymethyl cellulose.
[0061] Furthermore, the binder includes polyvinylidene fluoride. The reasonable use of the polyvinylidene fluoride binder not only enhances the internal bonding force of the diaphragm, making the diaphragm structure more solid, but also improves the overall stability of the diaphragm.
[0062] In one example, the steps of preparing the carboxyl-modified diamond include:
[0063] Heat-treating the nanodiamond in air or oxygen environment to prepare the carboxyl-modified diamond;
[0064] Wherein, the surface of the nano-diamond has one or more of hydroxyl, carbonyl and carboxyl functional groups.
[0065] The nanodiamond having one or more of hydroxyl, carbonyl and carboxyl functional groups on the surface is subjected to heat treatment, which can further activate the carboxyl group and promote the transformation of hydroxyl and carboxyl groups into carboxyl groups. The heat treatment helps to remove impurities on the surface of the nanodiamond and promotes the oxidation of the surface of the nanodiamond, thereby introducing more oxygen-containing functional groups.
[0066] In one example, the process parameters of the heating treatment include: heating to 400°C~450°C at a heating rate of 3°C / min~5°C / min, and keeping the temperature for 4h~10h.
[0067] It is understood that the heating rate in the heating treatment step can be selected from any value between 3°C / min and 5°C / min. For example, the heating rate includes but is not limited to 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min or 5°C / min. The insulation temperature includes but is not limited to 400°C, 410°C, 420°C, 430°C, 440°C or 450°C. The insulation time includes but is not limited to 4h, 5h, 6h, 7h, 8h, 9h or 10h.
[0068] In the present application, the source of nano-diamonds can be commercially available or homemade, as long as the surface of the nano-diamonds has one or more of hydroxyl, carbonyl and carboxyl functional groups.
[0069] For example, the steps for preparing nanodiamonds in the present application include:
[0070] a1. Take the carbon source trinitrotoluene and the pressurizing agent cyclotrimethylene trinitramine in a mass ratio of (70-40): (30-60) to obtain the explosive.
[0071] a2. Detonate the object to be exploded in a sealed explosion chamber filled with a cooling medium, wherein the ratio of the volume of the object to be exploded to the volume of the sealed explosion chamber is (0.1-0.5):1; prepare black powder.
[0072] a3. Using hydrochloric acid to heat the black powder to remove metal impurities in the black powder. Using oxidation to remove graphite and carbon to prepare the nano-diamond.
[0073] It is understandable that the above oxide can be oxidized by liquid phase oxidation or gas phase oxidation. During the oxidation process, the black powder gradually changes from black to light gray, and light gray nano diamond powder can be prepared. The infrared spectrum shows that the diamond surface prepared by this preparation method has a variety of oxygen-containing functional groups. Among them, the oxygen-containing functional groups include hydroxyl, carbonyl, carboxyl, ester, ether, etc. The coverage area of the oxygen-containing functional groups accounts for 10% to 20% of the surface of the nano diamond.
[0074] In one example, the thickness of the diaphragm is 150 μm to 500 μm. For example, the thickness of the diaphragm includes but is not limited to 150 μm, 180 μm, 200 μm, 220 μm, 240 μm, 260 μm, 280 μm, 300 μm, 330 μm, 350 μm, 380 μm, 400 μm, 430 μm, 450 μm, 480 μm or 500 μm.
[0075] In a second aspect of the present application, there is provided a method for preparing the diaphragm described in any example of the first aspect of the present application, comprising the following steps:
[0076] S10, mixing the carboxyl-modified diamond, the aluminate coupling agent, the carboxylate compound and the binder in a solvent to prepare a mixed slurry;
[0077] S20, forming the mixed slurry into a film, and drying it to prepare the diaphragm.
[0078] In one example, in step b1, the carboxyl-modified diamond, the aluminate coupling agent, the carboxylate compound and the binder are mixed in a solvent to prepare a mixed slurry, comprising:
[0079] b1, mixing the carboxyl-modified diamond and the aluminate coupling agent in a first solvent to prepare a first mixed solution;
[0080] b2, mixing the binder with a second solvent to prepare a second mixed solution;
[0081] b3. Mix the first mixed solution and the second mixed solution, add the carboxylate compound and mix them to prepare a mixed slurry.
[0082] It is understandable that the mixing of each step can be independently performed at room temperature or under heating conditions. For example, the process parameters for mixing under heating conditions include: heating to 40° C. to 70° C. for mixing.
[0083] For example, in step b3, the process parameters for adding the carboxylate compound and mixing include: mixing at 55° C. to 65° C.
[0084] In one example, in the mixed slurry, the mass volume ratio of the aluminate coupling agent to the solvent is (0.005-0.1) g: 1 mL. In the mixed slurry, the mass volume ratio of the aluminate coupling agent to the solvent includes but is not limited to 0.007 g: 1 mL, 0.008 g: 1 mL, 0.009 g: 1 mL, 0.01 g: 1 mL, 0.011 g: 1 mL, 0.015 g: 1 mL, 0.02 g: 1 mL, 0.04 g: 1 mL, 0.06 g: 1 mL, 0.08 g: 1 mL or 0.1 g: 1 mL.
[0085] In the preparation method of the present application, the amount of solvent used and the heating treatment temperature of the nanodiamond are both reduced, which effectively reduces energy consumption and reduces the incorporation of impurities.
[0086] In one example, the solvent, the first solvent and the second solvent are each independently selected from one or more of N-methylpyrrolidone, N,N-dimethylacetamide and N,N-dimethylformamide.
[0087] In one example, the mixed slurry is formed into a film, and after drying, the step of preparing the diaphragm includes: coating the mixed slurry on the surface of the substrate, and after drying, preparing the diaphragm.
[0088] In one example, the method for preparing the diaphragm further includes:
[0089] The substrate loaded with the diaphragm is immersed in water, and after the diaphragm is separated from the substrate, a drying process is performed.
[0090] Furthermore, the method for preparing the diaphragm provided in the present application comprises the following steps:
[0091] S100, heat-treating the nanodiamond in an air or oxygen environment to prepare the carboxyl-modified diamond; wherein the surface of the nanodiamond has one or more of hydroxyl, carbonyl and carboxyl functional groups; the process parameters of the heat treatment include: heating to 400°C~450°C at a heating rate of 3°C / min~5°C / min, and keeping the temperature for 4h~10h.
[0092] S200, mixing the carboxyl-modified diamond and the aluminate coupling agent in a first solvent to prepare a first mixed solution.
[0093] S300, mixing the binder with a second solvent to prepare a second mixed solution.
[0094] S400, mixing the first mixed solution and the second mixed solution, adding a carboxylic acid ester compound and mixing, to prepare a mixed slurry.
[0095] S500, coating the mixed slurry on the surface of a substrate, and drying the mixed slurry to prepare the diaphragm.
[0096] S600, soaking the substrate loaded with the diaphragm in water, and performing a drying process after the diaphragm is separated from the substrate.
[0097] In a third aspect of the present application, a secondary battery is provided, comprising a positive electrode sheet, a negative electrode sheet, a separator separated between the positive electrode sheet and the negative electrode sheet, and an electrolyte; the separator is the separator described in any example of the first aspect of the present application.
[0098] For example, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductor.
[0099] Wherein, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0100] For example, the positive electrode active material is not limited to lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), lithium cobalt phosphate (LiCoPO4), iron pyrophosphate (Li2FeP2O7), lithium cobalt oxide (LiCoO2), spinel lithium manganese oxide (LiMn2O4), spinel nickel lithium manganese oxide (LiNi 0.5 Mn 1.5 O4), layered lithium manganese oxide (LiMnO2), lithium nickel oxide (LiNiO2), lithium niobate (LiNbO2), lithium ferrite (LiFeO2), lithium magnesium oxide (LiMgO2), lithium calcium oxide (LiCaO2), lithium copper oxide (LiCuO2), lithium zinc oxide (LiZnO2), lithium molybdenum oxide (LiMoO2) and lithium tantalate (LiTaO2).
[0101] For example, the positive electrode binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0102] For example, the positive electrode conductive agent includes one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0103] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material, a negative electrode conductive agent and a negative electrode binder.
[0104] For example, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0105] Illustratively, the negative electrode active material includes one or more of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate.
[0106] Illustratively, the negative electrode binder includes one or more of styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid, and carboxymethyl chitosan.
[0107] Illustratively, the negative electrode conductive agent includes one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0108] The electrolyte can be in liquid, gel or solid state.
[0109] In one example, the electrolyte is an electrolyte solution, which includes a lithium salt and a solvent.
[0110] In one example, the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0111] In one example, the solvent includes one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0112] A fourth aspect of the present application provides an electrical device comprising the secondary battery described in the third aspect of the present application.
[0113] The following further specific examples are provided to explain the present application in detail. It should also be understood that the following examples are only used to further explain the present application and cannot be understood as limiting the scope of protection of the present application. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present application belong to the scope of protection of the present application. The specific process parameters of the following embodiments are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not necessarily limited to the specific values of the embodiments below.
[0114] [raw material]
[0115] The preparation method of nano-diamond includes: taking carbon source trinitrotoluene and pressurizing material cyclotrimethylene trinitramine in a mass ratio of 70:30 to obtain an explosive. The explosive is exploded in a sealed explosion chamber equipped with a cooling medium, and the volume ratio of the explosive to the sealed explosion chamber is 0.5:1; preparing black powder; using hydrochloric acid to heat the black powder to remove metal impurities in the black powder. Using an oxidation method to remove graphite and carbon to prepare nano-diamond. The surface of the nano-diamond has oxygen-containing functional groups such as hydroxyl, carbonyl, carboxyl, ester, and ether.
[0116] Aluminate coupling agent: Model: Aluminate coupling agent LS821, purchased from: Hubei Longxin Chemical Industry Co., Ltd.;
[0117] Carboxylic acid ester compounds: dibutyl phthalate .
[0118] Example 1
[0119] Preparation of carboxyl-modified diamond: Nano-diamond powder was evenly spread in a porcelain boat to ensure uniformity of heat treatment. The device was placed in a small tubular furnace, and the temperature was gradually increased to 425°C at a rate of 3°C / min in an air atmosphere, and maintained at this temperature for 5 hours before naturally cooling to room temperature to prepare carboxyl-modified diamond.
[0120] Preparation of mixed slurry:
[0121] (1) 0.0533 g of carboxyl-modified diamond was mixed in 50 mL of N-methylpyrrolidone solvent, and then 1 g of aluminate coupling agent LS821 was added, and ultrasonic mixing was performed for 30 minutes. During this period, the system was taken out every 10 minutes and manually shaken for 3 minutes to ensure uniform mixing, thereby preparing a first mixed solution.
[0122] (2) 0.5065 g of polyvinylidene fluoride was mixed with 50 mL of N-methylpyrrolidone solvent and subjected to ultrasonic mixing for 30 minutes. During this period, the system was taken out every 10 minutes and manually shaken for 3 minutes to ensure uniform mixing, thereby preparing a second mixed solution.
[0123] (3) The first mixed solution and the second mixed solution were mixed, 0.25 g of dibutyl phthalate was added, and the mixture was placed in an oven at 60° C. to dissolve for 10 min to prepare a mixed slurry.
[0124] Preparation of diaphragm:
[0125] The mixed slurry was evenly coated on a clean glass substrate using a 300 μm scraper, and then placed in an 80°C oven for 4 hours to remove the solvent. After drying, the sample was immersed in deionized water for 40 minutes to separate from the substrate, i.e., to remove the membrane. After that, the membrane was placed in a vacuum oven to dry to completely remove the residual moisture to complete the preparation of the membrane. The scanning electron microscope image of the membrane prepared in Example 1 is shown in FIG. Figure 1 shown.
[0126] Example 2
[0127] Preparation of carboxyl-modified diamond: Nano-diamond powder was evenly spread in a porcelain boat to ensure uniformity of heat treatment. The device was placed in a small tubular furnace, and the temperature was gradually increased to 425°C at a rate of 5°C / min, and maintained at this temperature for 5 hours before naturally cooling to room temperature to prepare carboxyl-modified diamond.
[0128] Preparation of mixed slurry:
[0129] (1) 0.0598 g of carboxyl-modified diamond was mixed in 50 mL of N-methylpyrrolidone solvent, and then 0.9 g of aluminate coupling agent LS821 was added, and ultrasonic mixing was performed for 40 minutes. During this period, the system was taken out every 10 minutes and manually shaken for 5 minutes to ensure uniform mixing, thereby preparing a first mixed solution.
[0130] (2) 0.5086 g of polyvinylidene fluoride was mixed with 50 mL of N-methylpyrrolidone solvent and subjected to ultrasonic mixing for 40 minutes. During this period, the system was taken out every 10 minutes and manually shaken for 5 minutes to ensure uniform mixing, thereby preparing a second mixed solution.
[0131] (3) The first mixed solution and the second mixed solution were mixed, 0.27 g of dibutyl phthalate was added, and the mixture was dissolved in an oven at 60° C. for 10 min to prepare a mixed slurry.
[0132] Preparation of diaphragm:
[0133] The mixed slurry was evenly coated on a clean glass substrate using a 250 μm scraper, and then placed in an 80°C oven for 4 hours to remove the solvent. After drying, the sample was immersed in deionized water for 50 minutes to separate from the substrate, i.e., to remove the membrane. After that, the membrane was placed in a vacuum oven to dry to completely remove the residual moisture to complete the preparation of the membrane. The actual picture of the membrane prepared in Example 2 is shown in FIG. Figure 2 shown.
[0134] Example 3
[0135] Preparation of carboxyl-modified diamond: Nano-diamond powder was evenly spread in a porcelain boat to ensure uniformity of heat treatment. The device was placed in a small tubular furnace, and the temperature was gradually increased to 425°C at a rate of 3°C / min, and maintained at this temperature for 5 hours before naturally cooling to room temperature to prepare carboxyl-modified diamond.
[0136] Preparation of mixed slurry:
[0137] (1) 0.0502 g of carboxyl-modified diamond was mixed in 50 mL of N-methylpyrrolidone solvent, and then 1 g of aluminate coupling agent LS821 was added, and ultrasonic mixing was performed for 50 minutes. During this period, the system was taken out every 10 minutes and manually shaken for 3 minutes to ensure uniform mixing, thereby preparing a first mixed solution.
[0138] (2) 0.4990 g of polyvinylidene fluoride was mixed with 50 mL of N-methylpyrrolidone solvent and subjected to ultrasonic mixing for 50 minutes. During this period, the system was taken out every 10 minutes and manually shaken for 3 minutes to ensure uniform mixing, thereby preparing a second mixed solution.
[0139] (3) The first mixed solution and the second mixed solution were mixed, 0.24 g of dibutyl phthalate was added, and the mixture was placed in an oven at 60° C. to dissolve for 10 min to prepare a mixed slurry.
[0140] Preparation of diaphragm:
[0141] The mixed slurry was evenly coated on a clean glass substrate using a 400 μm scraper, and then placed in an 80°C oven for 4 hours to remove the solvent. After drying, the sample was immersed in deionized water for 50 minutes to separate from the substrate, i.e., de-filming. After that, the membrane was placed in a vacuum oven to dry to completely remove residual moisture to complete the preparation of the membrane.
[0142] Example 4
[0143] Preparation of carboxyl-modified diamond: Nano-diamond powder was evenly spread in a porcelain boat to ensure uniformity of heat treatment. The device was placed in a small tubular furnace, and the temperature was gradually increased to 425°C at a rate of 5°C / min, and maintained at this temperature for 5 hours before naturally cooling to room temperature to prepare carboxyl-modified diamond.
[0144] Preparation of mixed slurry:
[0145] (1) 0.0507 g of carboxyl-modified diamond was mixed in 50 mL of N-methylpyrrolidone solvent, and then 0.8 g of aluminate coupling agent LS821 was added, and ultrasonic mixing was performed for 40 minutes. During this period, the system was taken out every 10 minutes and manually shaken for 5 minutes to ensure uniform mixing, thereby preparing a first mixed solution.
[0146] (2) 0.4985 g of polyvinylidene fluoride was mixed with 50 mL of N-methylpyrrolidone solvent and subjected to ultrasonic mixing for 40 minutes. During this period, the system was taken out every 10 minutes and manually shaken for 5 minutes to ensure uniform mixing, thereby preparing a second mixed solution.
[0147] (3) The first mixed solution and the second mixed solution were mixed, 0.26 g of dibutyl phthalate was added, and the mixture was placed in an oven at 60° C. to dissolve for 10 min to prepare a mixed slurry.
[0148] Preparation of diaphragm:
[0149] The mixed slurry was evenly coated on a clean glass substrate using a 450 μm scraper, and then placed in an 80 ° C oven for 4 hours to remove the solvent. After drying, the sample was immersed in deionized water for 50 minutes to separate from the substrate, i.e., demolding. After that, the membrane was placed in a vacuum oven to dry to completely remove residual moisture to complete the preparation of the membrane.
[0150] Comparative Example 1
[0151] Preparation of mixed slurry:
[0152] 0.5 g of polyvinylidene fluoride was mixed with 50 mL of N-methylpyrrolidone solvent, and ultrasonic mixing was performed for 30 minutes. During this period, the system was taken out every 10 minutes for manual shaking for 3 minutes to ensure uniform mixing, and a mixed solution was prepared. Then 0.26 g of dibutyl phthalate was added and dissolved in a 60°C oven for 10 minutes to prepare a mixed slurry.
[0153] Preparation of diaphragm:
[0154] The mixed slurry was evenly coated on a clean glass substrate using a 300 μm scraper, and then placed in an 80°C oven for 4 hours to remove the solvent. After drying, the sample was immersed in deionized water for 30 minutes to separate from the substrate, i.e., de-filming. After that, the membrane was placed in a vacuum oven to dry to completely remove residual moisture to complete the preparation of the membrane.
[0155] Comparative Example 2
[0156] Preparation of mixed slurry:
[0157] (1) 0.0533 g of carboxyl-modified diamond powder was mixed with 50 mL of N-methylpyrrolidone solvent, and then 1 g of coupling agent γ-aminopropyltriethoxysilane was added, and ultrasonic mixing was performed for 30 minutes. During this period, the system was taken out every 10 minutes and manually shaken for 3 minutes to ensure uniform mixing, thereby preparing a first mixed solution.
[0158] (2) 0.5065 g of polyvinylidene fluoride was mixed with 50 mL of N-methylpyrrolidone solvent and subjected to ultrasonic mixing for 30 minutes. During this period, the system was taken out every 10 minutes and manually shaken for 3 minutes to ensure uniform mixing, thereby preparing a second mixed solution.
[0159] (3) The first mixed solution and the second mixed solution were mixed, 0.25 g of dibutyl phthalate was added, and the mixture was placed in an oven at 60° C. to dissolve for 10 min to prepare a mixed slurry.
[0160] Preparation of diaphragm:
[0161] The mixed slurry was evenly coated on a clean glass substrate using a 300 μm scraper, and then placed in an 80°C oven for 4 hours to remove the solvent. After drying, the sample was immersed in deionized water for 40 minutes to separate from the substrate, i.e., de-filming. After that, the membrane was placed in a vacuum oven to dry to completely remove residual moisture to complete the preparation of the membrane.
[0162] Comparative Example 3
[0163] Preparation of carboxyl-modified diamond: Nano-diamond powder was evenly spread in a porcelain boat to ensure uniformity of heat treatment. The device was placed in a small tubular furnace, and the temperature was gradually increased to 425°C at a rate of 3°C / min, and maintained at this temperature for 5 hours before naturally cooling to room temperature to prepare carboxyl-modified diamond.
[0164] Preparation of mixed slurry:
[0165] (1) 0.0533 g of carboxyl-modified diamond was mixed in 50 mL of N-methylpyrrolidone solvent, and then 1 g of aluminate coupling agent LS821 was added, and ultrasonic mixing was performed for 30 minutes. During this period, the system was taken out every 10 minutes and manually shaken for 3 minutes to ensure uniform mixing, thereby preparing a first mixed solution.
[0166] (2) 0.5065 g of polyvinylidene fluoride was mixed with 50 mL of N-methylpyrrolidone solvent and subjected to ultrasonic mixing for 30 minutes. During this period, the system was taken out every 10 minutes and manually shaken for 3 minutes to ensure uniform mixing, thereby preparing a second mixed solution.
[0167] (3) The first mixed solution and the second mixed solution were mixed, and 0.25 g of plasticizer dioctyl epoxytetrahydrophthalate was added, and the mixture was placed in an oven at 60° C. to dissolve for 10 min to prepare a mixed slurry.
[0168] Preparation of diaphragm:
[0169] The mixed slurry was evenly coated on a clean glass substrate using a 300 μm scraper, and then placed in an 80°C oven for 4 hours to remove the solvent. After drying, the sample was immersed in deionized water for 40 minutes to separate from the substrate, i.e., de-filming. After that, the membrane was placed in a vacuum oven to dry to completely remove residual moisture to complete the preparation of the membrane.
[0170] Test Case
[0171] Contact angle: An electrolyte containing 1 mol / L LiPF6, 89 vol% DEC / EC (1:1), 1 vol% VC and 10% FEC additives was selected, and the contact angle performance of the diaphragm and the electrolyte was measured using a German Kruss DSA100 video optical contact angle meter. The contact angle performance of the diaphragm prepared in Example 3 and the electrolyte is shown in the figure below: Figure 3 shown.
[0172] Cycling performance: The diaphragms prepared in the examples and comparative examples were assembled into silicon negative electrode half-cells, and the cycling performance graphs of the silicon negative electrode half-cells were tested at a charge and discharge rate of 0.5C. The cycling performance graphs of the diaphragms prepared in the examples 1 and comparative examples 1 were assembled into silicon negative electrode half-cells as shown in FIG. Figure 4 shown.
[0173] Depend on Figure 1 It can be seen that the diaphragm prepared in the present application still has good porosity without adding polyolefin. Figure 3 It can be seen that the diaphragm prepared in the present application has good wettability with the electrolyte. Figure 4 When the diaphragm prepared in Example 1 is assembled into a silicon negative electrode half-cell, it has a more excellent specific capacity and coulombic efficiency, and its cycle stability is more excellent.
[0174] Figure 5 This is a real shot of the diaphragm prepared in Comparative Example 2. Figure 6 This is a real shot of the diaphragm prepared in Comparative Example 3. Figure 5 and Figure 6 It can be seen that the diaphragm prepared in Comparative Example 2 did not use an aluminate coupling agent, and the diaphragm prepared in Comparative Example 3 did not use a carboxylate compound, resulting in poor mechanical properties of the diaphragms prepared in Comparative Examples 2 and 3, as shown in the actual photos, the diaphragms are fragile.
[0175] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0176] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.
Claims
1. A diaphragm, characterized in that: The diaphragm comprises carboxyl-modified diamond, an aluminate coupling agent, a carboxylate compound and a binder in a mass ratio of (0.04-0.06): (0.8-1.2): (0.2-0.3): (0.4-0.6); Wherein, the carboxylic acid ester compound includes one or more compounds having the structure shown in formula (I): ; R 11 and R 12 Each independently selected from C3~C 10 Alkyl or C3~C 10 Ar is selected from S1 substituted or unsubstituted C6~C 20 Aromatic group; S1 is selected from C1~C 10 Alkyl, C1~C 10 Haloalkyl or ; R 13 Selected from C3~C 10 Alkyl or C3~C 10 Halogenated alkyl.
2. The diaphragm according to claim 1, characterized in that R 11 and R 12 Each is independently selected from C3~C8 alkyl; Ar is selected from C6~C 10 Aromatic group.
3. The diaphragm according to claim 1, characterized in that The carboxylic acid ester compound includes one or more compounds having the structure shown in formula (II): ; m1 and m2 are each independently 1, 2, 3, 4 or 5.
4. The diaphragm according to any one of claims 1 to 3, characterized in that: The aluminate coupling agent includes one or more of aluminate coupling agent LS60, aluminate coupling agent LS62, aluminate coupling agent LS821 and aluminate coupling agent NXH-821.
5. The diaphragm according to any one of claims 1 to 3, characterized in that: The binder includes one or more of polyvinylidene fluoride, styrene-butadiene rubber and carboxymethyl cellulose.
6. The diaphragm according to any one of claims 1 to 3, characterized in that: The preparation steps of the carboxyl-modified diamond include: Heat-treating the nanodiamond in air or oxygen environment to prepare the carboxyl-modified diamond; The surface of the nano-diamond has one or more of hydroxyl, carbonyl and carboxyl functional groups; the process parameters of the heating treatment include: heating to 400°C~450°C at a heating rate of 3°C / min~5°C / min, and keeping the temperature for 4h~10h.
7. A method for preparing a diaphragm according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mixing the carboxyl-modified diamond, the aluminate coupling agent, the carboxylate compound and the binder in a solvent to prepare a mixed slurry; The mixed slurry is formed into a film and dried to prepare the separator.
8. The method for preparing a diaphragm according to claim 7, characterized in that: In the mixed slurry, the mass volume ratio of the aluminate coupling agent to the solvent is (0.005-0.1) g:1 mL.
9. A secondary battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator between the positive electrode sheet and the negative electrode sheet, and an electrolyte; wherein the separator is the separator according to any one of claims 1 to 6.
10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.
Citation Information
Patent Citations
Battery separator, method for manufacture thereof, and lithium secondary battery
CN103165842A
Diaphragm containing organic-inorganic coating for lithium battery and preparation method of same
CN110492043A
Polyvinylidene fluoride-hexafluoropropylene / cellulose / titanium dioxide composite membrane and preparation method and application thereof
CN110581249A
Nano composite polyethylene film as well as preparation method and application thereof
CN116444882A
Puncture-resistant diaphragm modified by electronegative nano-diamond and preparation method of puncture-resistant diaphragm
CN118867561A